Efficacy of Granulocyte and Monocyte Adsorption Apheresis for Treatment of Palmoplantar Pustulosis. Issue 3 (June 2014) - Fujisawa, Tomomi; Tawada, Chisato; Mizutani, Yoko; Doi, Tomoaki; Yoshida, Shozo; Ogura, Shinji; Seishima, Mariko
Abstract Palmoplantar pustulosis (PPP) is characterized by neutrophilic pustules with erythema, which are limited to the hands and feet. Although granulocyte and monocyte adsorption apheresis (GMA) has shown remarkable effects on generalized pustular psoriasis, there are few reports of PPP treated with GMA. We treated three refractory PPP patients using GMA weekly for 5 weeks. The skin eruptions were assessed by a 5‐grade score for scales, pustules, and erythema. GMA decreased the total grade from 9 to 2 in patients 1 and 2, and from 7 to 3 in patient 3. The GMA effects were estimated to be excellent in all three patients. Pustule formation and pain disappeared in all cases. The treatment effect lasted for at least 5 months after GMA. GMA was also effective for relieving the arthralgia in one patient, but it recurred at 6 weeks. Based on these findings, GMA could be an effective therapy for refractory PPP.